Between Democracy and Islam: The Rise of Islamists’ Political Awareness in Jordan Between 2011 to 2024 and Its Effects on Religious, National, and Political Identities - Yael Keinan-Cohen; Gadi Hitman; Elad Ben-Dror (Religions)
This article traces the strengthening of Muslim movements in Jordan, emphasizing the period that marked the beginning of the regional upheaval (2011). It aims to examine whether and how this strengthening affected religious, national, and political identities. The article examines the interrelationships between the Hashemite regime and the Salafi movements in Jordan during and after the Arab Spring. This examination shows that there was a deterioration, aggravation, and erosion in these relations, on the one hand, and, on the other hand, also an understanding on the part of the regime that despite this the Salafis are interested in taking part in the Jordanian political game. In this discourse between the Salafi movements and the regime, we will also examine whether the movements sought to change the regime’s nature and, thus, the nature of society in Jordan from a Hashemite national identity to a Salafi identity. The article is based on secondary and primary sources that unfold a fascinating picture of dialectics and dialog between the ideological extremes of democracy and Islam. The main findings are that these processes, during and after the Arab Spring, tend to contain religious groups that will also participate in politics, out of recognition of the supremacy of the law of the state, which is not necessarily religious.